The Impact of the Reconstruction of Coastal Tourist Attractions and Tourist Visits on Employment Absorption and Community Income in the Mataram City - Mukmin, Mukmin; Dewi, Novi Yanti Sandra; Agustina, Ahadiah (Universitas Hamzanwadi, 2024)
The importance of beach tourism attractions in driving the economy of a region makes it a primary focus in efforts to increase community income. This research aims to evaluate the impact of beach tourism attraction reconstruction and the number of tourist visits on increasing employment opportunities and community income. This research adopts a quantitative approach using surveys as the data collection tool. The research sample consists of 109 respondents, comprising 45 males and 64 females. The research instrument used is a Likert scale questionnaire consisting of 25 statements based on research indicators. Data analysis is conducted using multiple linear regression with two stages of testing. The results of the data analysis in the first stage indicate that beach attraction reconstruction and the number of tourist visits contribute 50.9% to employment absorption. Furthermore, the results of the analysis in the second stage indicate that beach attraction reconstruction and the number of tourist visits contribute 44.3% to community income. The findings of this research are expected to provide guidance for decision-makers in planning the development of the tourism sector in Mataram City